Quadrivalent HPV (4vHPV) vaccine immunogenicity and safety in women using immunosuppressive drugs due to solid organ transplant - Miyaji, Karina Takesaki; Infante, Vanessa; Picone, Camila Melo; Dillner, Joakim; Kann, Hanna; Eklund, Carina; Levi, José Eduardo; de Oliveira, Ana Carolina Soares; Lara, Amanda Nazareth; Kawakami, Lyca Suzuki; Tacla, Maricy; Castanheira, Cristina Paula; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionImmunocompromised persons are at high risk of persistent Human Papilloma Virus (HPV) infection and associated diseases. Few studies evaluated HPV vaccines in immunocompromised persons. This study aimed to evaluate the quadrivalent HPV vaccine (4vHPV) immunogenicity and safety in solid organ transplant (SOT) recipients, in comparison to immunocompetent women (IC).MethodsOpen-label clinical trial that enrolled SOT recipients and immunocompetent women aged 18 to 45 years. All participants received three doses of 4vHPV vaccine. Blood samples were drawn for evaluation of immune responses at baseline and one month after the third vaccination. Seroconversion rates and antibody geometric mean concentration (GMC) against HPV 6, 11, 16, 18, 31, 35, 52 and 58 were measured with in-house multiplexed serology assay (xMAP technology). Follow-up for the local and systemic adverse events (AEs) continued for seven days after each vaccination. Severe AEs were evaluated throughout the study.Results125 SOT and 132 immunocompetent women were enrolled; 105 (84%) SOT and 119 (90%) immunocompetent women completed the study. At baseline, HPV seropositivity was not significantly different between groups. Seroconversion rates were significantly lower in SOT (HPV18, 57%; HPV6 and 16, 69%; and HPV11, 72%) than in immunocompetent women (100% seroconversion to all vaccine types) (p<0.001). Antibody GMCs of all four HPV vaccine types were also significantly lower in SOT (p<0.001). Pain in the injection site and headache were the most frequent adverse event in both groups. Local pain was more frequent in immunocompetent women than in SOT recipients. Rates of other AEs were comparable in both groups.Conclusion4vHPV vaccine was well-tolerated by SOT recipients. We found strong evidence of lower humoral immune responses to 4vHPV vaccine in SOT compared to immunocompetent women, which strengthen recommendation of routine cervical cancer screening in SOT recipients regardless of HPV vaccination status.